Control del proceso de pago en el Departamento Financiero del Gobierno Autónomo Descentralizado Provincial de Los Ríos - Vera Tello, Maira Alejandra (2018)
The Provincial Decentralized Autonomous Government of Los Ríos is a public institution, which is responsible for carrying out works that contribute to the development of the province, this GAD was chosen to carry out the present case study with the theme "CONTROL OF THE PROCESS OF PAYMENT IN THE FINANCIAL DEPARTMENT OF THE GAD PROVINCIAL DE LOS RÍOS ". The development of this research corresponds to the guidelines required by the Technical University of Babahoyo, to comply with the titling process, choosing as a complex examination modality prior to obtaining the degree in Accounting and Auditing; for which I applied the knowledge that was acquired during the race. The financial department is part of the organizational structure of this Provincial GAD, which is responsible for "financial resources are managed and controlled in an appropriate manner to support the management of the Provincial Government in accordance with current regulations and provide accurate and timely information for the correct decision-making "(GADPLR, ORGANIC STATUTE OF ORGANIZATIONAL MANAGEMENT BY PROCESSES OF THE AUTONOMOUS, DECENTRALIZED GOVERNMENT OF LOS RÍOS, 2015). This work is related to the line of research Management of Accounting Information, the information obtained in this case study was through the deductive research method, through interviews conducted with people involved in current processes; For this, the codes and laws related to the present investigation will be analyzed. The present case study is carried out with the purpose of following up the payment process to suppliers and employees in the financial department of the Provincial GAD of Los Ríos and to know in this way, if an adequate control of the procedures is carried out and if apply two policies or other forms of control to Financial Management that will allow the correct use of financial resources, thus achieving to reduce unnecessary processes, time and costs; An analysis of the functions manual of the Provincial GAD is also carried out.